FACTORS INFLUENCING STUDENTS’ SPEAKING ANXIETY AT ONE PUBLIC UNIVERSITY IN JAMBI: PERSONALITY TRAITS, MOTIVATION, AND FAMILY ENVIRONMENT ASPECTS: Personality Traits, Motivation, and Family Environment Aspects. - Miftahudin; Mukhlash Abrar; Habizar (JAMBI-ENGLISH LANGUAGE TEACHING, 2022)
This research aimed to describe factors that influence students’ speaking anxiety and to explore the strategies used by the students to overcome their anxiety. The site of this research was at one public university in Jambi. The researcher utilised purposive sampling technique in selecting the participants. There were 12 participants of this research which including 7th semester students, 5th semester students, and 3rd semester students who have passed speaking classes. This research employed qualitative study with case study approach in one English teacher study program. In collecting the data, the researcher used interview and documentation as the data collection. The results of this research indicated that there were still several factors faced by the students which influenced their speaking anxiety. Those factors were afraid, shy, unconfident, overthinking, nervous, mood, low motivation, and family support. The most factors felt by the students were overthinking and unconfident. This research also pointed out that the participants used several strategies to overcome their anxiety in speaking. There were 9 strategies employed by the participants including taking a deep breathe, practicing, being confident, calming down, studying hard, being well-prepared, being alone, discussing with friends, and getting motivation from friends.